Harnessing landfill gas (LFG) for electricity: A strategy to mitigate greenhouse gas (GHG) emissions in Jakarta (Indonesia). (1st January 2022) - Kurniawan, Tonni Agustiono; Liang, Xue; Singh, Deepak; Othman, Mohd Hafiz Dzarfan; Goh, Hui Hwang; Gikas, Petros; Kern, Axel Olaf; Kusworo, Tutuk Djoko; Shoqeir, Jawad A.
Abstract: Due to its increasing demands for fossil fuels, Indonesia needs an alternative energy to diversify its energy supply. Landfill gas (LFG), which key component is methane (CH4 ), has become one of the most attractive options to sustain its continued economic development. This exploratory study seeks to demonstrate the added value of landfilled municipal solid waste (MSW) in generating sustainable energy, resulting from CH4 emissions in the Bantargebang landfill (Jakarta). The power generation capacity of a waste-to-energy (WTE) plant based on a mathematical modeling was investigated. This article critically evaluated the production of electricity and potential income from its sale in the market. The project's environmental impact assessment and its socio-economic and environmental benefits in terms of quantitative and qualitative aspects were discussed. It was found that the emitted CH4 from the landfill could be reduced by 25, 000 Mt annually, while its electricity generation could reach one million kW ⋅ h annually, savings on equivalent electricity charge worth US 112 million/year (based on US' 8/kW ⋅ h). An equivalent CO2 mitigation of 3.4 × 10 6 Mt/year was obtained. The income from its power sale were US 1.2 × 10 6 in the 1 st year and 7.7 × 10 7 US in the 15 th year, respectively, based on the projected CH4 and power generation. The modeling study on the Bantargebang landfill using the LFG extraction data indicated that the LFG production ranged from 0.05 to 0.40 m 3 per kg of the landfilled MSW. The LFG could generate electricity as low as US' 8 per kW ⋅ h. With respect to the implications of this study, the revenue not only defrays the cost of landfill's operations and maintenance (O&M), but also provides an incentive and means to further improve its design and operations. Overall, this work not only leads to a diversification of primary energy, but also improves environmental protection and the living standard of the people surrounding the plant. Graphical abstract: Image 1 Highlights: The emitted CH4 in the studied landfill could be reduced by 25, 000 Mt/year. Waste to energy conversion diversifies primary energy in Indonesia. Revenue from biogas defrays the cost of landfill's operations and maintenance. The revenue provides an incentive to improve landfills' design and operations.